Basal ganglia calcification in Down's syndrome. Issue 1 (January 1985) - Takashima, S; Becker, L E
Abstract : The basal ganglia from 33 patients (all over one year of age) with Down's syndrome were examined pathologically. Forty-five per cent had calcification. Basal ganglia calcification was localised to a constant area of globus pallidus and became more prominent with increased age. Calcification and amyloid degeneration of the adjacent blood vessels were present. The proximity of abnormal blood vessels to basal ganglia calcification suggests a pathogenetic relationship.